A regionally specific drinking custom 'Otōri' and its association with alcohol consumption/alcohol use disorders: a cross-sectional study. Issue 5 (13th May 2021) - Sugiyama, Yoshifumi; Yoshimoto, Hisashi; Iwabuchi, Keisuke; Matsushima, Masato
Abstract : Objectives: The primary objective was to describe the characteristics of Otōri, a regionally specific drinking custom in the Miyakojima region of Okinawa, Japan, and its participants. The secondary objective was to clarify the distribution of alcohol consumption/alcohol use disorders as measured by the Alcohol Use Disorders Identification Test (AUDIT) and its association with the frequency of engagement in Otōri per month. Design: Cross-sectional study. Setting: Tarama Island, a remote island in Okinawa, Japan. Participants: Individuals who lived on Tarama Island, participated in a mass general health check or mass influenza vaccination programme, were aged ≥20 years and had decision-making capacity were eligible to participate. Primary outcome measures: Alcohol consumption/alcohol use disorders as measured by the AUDIT, frequency of engagement in Otōri per month, settings in which people engage in Otōri and attitudes toward Otōri. Results: Among 478 eligible participants, 401 answered the questionnaire. Approximately 15% reported attitudes toward Otōri of 'like' or 'somewhat like'; around 80% of these participants were middle-aged to older adult men. Compared with the national average, a higher percentage of people (9.2% and 40.9% of women and men, respectively) had AUDIT scores indicating 'hazardous drinking or more', which was associated with 'low or intermediate frequency' and 'high frequency' of engagement in Otōri per month (ORs of 7.626 and 20.321, respectively). Conclusions: Social obligation generated by some community members could pressure most of the population into participating in Otōri, possibly leading to a higher percentage of people engaging in hazardous/harmful alcohol consumption and alcohol dependence. However, healthcare professionals should carefully consider the beneficial and detrimental effects of the custom on biomedical and social conditions and avoid advocating to promote or abolish the custom by only highlighting one aspect.